Psychological Distress As A Mediator Variable Between Experienced Incivility From Supervisor And Coworker To Instigated Incivility - Verasari, Metty; Hamzah, Hazalizah (International Journal for Educational and Vocational Studies, 2019)
Workplace Incivility is a common phenomenon in many organizations workplaces. The necessary antecedent of workplace incivility consisted of the presence of two or more people, with one or more as the source of the incivility, and another or others as its target in the workplace. Understanding the concept of workplace incivility to hospital managers and other health care organizations are very important for organizational development. This study aimed to understand the effect of experienced incivility from the nurse’s supervisor and coworker in the hospital. Including sacrificing the psychological well-being of workers to experience psychological stress. This psychological pressure can be stress, job dissatisfaction and can have a high level of burnout. The methodology to analyze is a diary study between 3 days on 102 nurses in Sumatra, Indonesia. The results of this study indicate that the psychological stress variable is not a variable between the experience of getting unpleasant treatment from superiors or work colleagues towards the emergence of impolite and intentional rude behavior.